Photonic Bound States in the Continuum in Si Structures with the Self‐Assembled Ge Nanoislands. Issue 7 (3rd June 2021) - Dyakov, Sergey A.; Stepikhova, Margarita V.; Bogdanov, Andrey A.; Novikov, Alexey V.; Yurasov, Dmitry V.; Shaleev, Mikhail V.; Krasilnik, Zakhary F.; Tikhodeev, Sergei G.; Gippius, Nikolay A.
Abstract: Germanium self‐assembled nanoislands and quantum dots are very prospective for CMOS‐compatible optoelectronic integrated circuits but their photoluminescence (PL) intensity is still insufficient for many practical applications. Here, it is demonstrated experimentally that the PL of Ge nanoislands in silicon photonic crystal slabs (PCS) with hexagonal lattice can be dramatically enhanced due to the involvement in the emission process of the bounds states in the continuum. These high‐Q photonic resonances allow to achieve PL resonant peaks with the quality factor as high as 2200 and with the peak PL enhancement factor of more than two orders of magnitude. The corresponding integrated PL enhancement is demonstrated to be more than one order of magnitude. This effect is studied theoretically by the Fourier modal method in the scattering matrix form. The symmetry of the quasi‐normal guided modes in the PCS is described in terms of group theory. This work paves the way toward a new class of optoelectronic components compatible with silicon technology. Abstract : The photoluminescence of germanium nanoislands in a silicon photonic crystal slab with a hexagonal lattice can be dramatically enhanced due to the bounds states in continuum. The corresponding quality factor of the peaks in the emission spectra is 2200 and the photoluminescence enhancement factor is more than 100. The symmetry of the eigenmodes is described in terms of group theory.